De Novo Interstitial Deletion of Chromosome 2 (p23p24) - Pen-Hua Su; Jia-Yuh Chen; Teng-Fu Tsao; Suh-Jen Chen (Elsevier, 2011)
Structural anomalies associated with partial 2p monosomy are rare. There has only been one case of interstitial deletion of 2p24.2-2p25.1 and three cases of 2p23.3-2p25.1 described in the literature. We report here the first instance of an interstitial deletion of 2p23p24, confirmed by comparative genome hybridization. We present a clinical and cytogenetic report of a patient with psychomotor retardation, hearing impairment, and limb abnormalities. The obvious osseous fusion with bone marrow and cortex continuation between proximal parts of radius and ulna-congenital radioulnar synostosis-were first visualized by multidetector-row computed tomography scan.